The Relationship Between Ovarian Cancer and Depressive Symptoms: A Case Report - Syahrul Gusnaldi Prawidya; Roosyidah; Anabela Amoreth Amsori; Novanthy Nur Rohmadhani Subagyo; Muhammad Azhari Baihaqi; Embun Kumalaratih; Hafid Algristian (Medicor : Journal of Health Informatics and Health Policy, 2026)
Ovarian cancer is a malignant tumor originating from the ovaries, affecting various age groups, with multiple histological types. Depression is a common mental disorder characterized by emotional and physical symptoms. Cancer diagnosis and treatment are widely recognized as major psychological stressors that can precipitate or exacerbate mental health disturbances, particularly depressive and anxiety disorders, due to the profound emotional, social, and physiological challenges experienced by patients. This case report highlights the relationship between ovarian cancer and depressive symptoms. This case report examines the relationship between ovarian cancer and depressive symptoms, with a focus on the psychological and inflammatory pathways influencing mental health. A 44-year-old woman presented with a loss of interest in activities, beginning three weeks after her ovarian cancer diagnosis. Research indicates that factors such as advanced cancer stage, poor physical functioning, and the absence or discontinuation of chemotherapy due to disease progression or treatment intolerance may increase the susceptibility to mental health disorders among ovarian cancer patients. Cancer patients, including those diagnosed with ovarian cancer, experience heightened stress and depression compared to those with non-neoplastic diseases. Depression can arise due to both psychological stress and inflammatory processes triggered by cancer treatments.